The utility of the subcuticular suture in hepatic resection - Inoue, Yoshihiro (Contemp Oncol (Pozn), 2018)
AIM OF THE STUDY: Despite recent technical progress and advances in the perioperative management of liver surgery, postoperative surgical site infection (SSI) is still one of the most common complications that extends hospital stays and increases medical expenses following hepatic surgery. MATERIAL AND METHODS: From 2001 to 2017 a total of 1180 patients who underwent hepatic resection for liver tumours were retrospectively analysed with respect to the predictive factor of superficial incisional SSI, using a propensity score matching by procedure (subcuticular or mattress suture). RESULTS: The incidence of superficial and deep incisional SSIs was found to be 7.1% (84/1180). By propensity score matching (PSM), 121 of the 577 subcuticular suture group patients could be matched with 121 of the 603 mattress suture group patients. Multivariate analysis demonstrated wound closure technique as the only independent risk factor that correlated significantly with the occurrence of superficial incisional SSIs (p = 0.038). C-reactive protein (CRP) levels on postoperative day 4 were significantly higher in patients with incisional SSIs than in those without (p < 0.001). CONCLUSIONS: Wound closure technique with subcuticular continuous spiral suture using absorbable suture should be considered to minimise the incidence of incisional SSIs. Moreover, wounds should be carefully checked when CRP levels are high on postoperative day 4.